Penggunaan LinkedIn untuk Personal Branding Karyawan - Audhiandra Nur Ratri Okviosa (ArtComm, 2022)
Currently, the existence of LinkedIn social media is often a means of displaying one's professional competence, especially in the field of work. This study aims to examine the use of LinkedIn for employee personal branding. The research approach used is qualitative with the case study method. The data collection technique used was interviews with 4 key informants who are private employees working for private companies in various fields, namely the technology industry, educational consulting, design, and banking. In addition, there were supporting informants consisting of 2 people who work as recruitment specialists. The results of the study show that the use of LinkedIn can construct one's identity as one's professional personal branding. Aspects that are focused on the formation of personal branding include (1) Displaying self-identity and activities in a professional manner, and (2) Awareness of the importance of developing self-image on LinkedIn as a means of social recognition